Early evaluation of use of fermented chicken manure products in practice of apple nutrient management - Tóth, Florence Alexandra; Tamás, János; Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2022)
According to the Green Deal efforts, the importance and relevance of organic fertilization will increase in the near future. Therefore, the investigation of the effects of different organic fertilizers on soil productivity and nutrient supply is a priority area of agricultural research. Organic fertilizer experiment was conducted in an eight-year-old apple (Malus domestica Borkh.) orchard at Debrecen-Pallag. In the trial Pinova cultivar was used. In this study, two different fermented chicken manure products were added to the soil (in 20 cm depth) to test their effects on soil nutrient status, plant uptake and fruit quality. It was found that the applied treatments slightly increased the pH and nutrient levels in almost all cases, but significant effect was not observed in all treatments compared to the control. Leaf nutrient contents (N, P, K, Ca and Mg) were measured in the experiment. Leaf nutrient status was not affected by the fermented chicken manure treatments. However, used treatments had strong effects on the fruit characteristics and inner parameters, such as fruit diameter and Brix value. Moreover, it was established that the applied organic fertilizers increased the yield significantly.